contestada

Percy solved the equation x2 + 7x + 12 = 12. His work is shown below. Is Percy correct? Explain.

1. (x + 3)(x + 4) = 12

2. x + 3 = 12 or x + 4 = 12

3. x = 9 or x = 8

Respuesta :

= > x² + 7x + 12 = 12

= > x² + ( 4 + 3 )x + 12 = 12

= > x² + 4x + 3x + 12 = 12

= > x( x + 4 ) + 3( x + 4 ) = 12

= > ( x + 4 ) ( x + 3 ) = 12


Percy did correct till this step. But by doing like this, Percy can't get the values of the variable x.



Percy should follow the following steps :

= > x² + 7x + 12 = 12


Add -12 on both sides,


= > x² + 7x + 12 - 12 = 12 - 12

= > x² + 7x = 0

= > x( x + 7 ) = 0

= > ( x = 0 ) or ( x + 7 = 0 )

= > ( x = 0 ) or ( x = - 7 )



Hence, required value(s) of x is 0 or -7
[tex].[/tex]

Sample Response: Percy is not correct because he applied the zero product property to a factored expression that was not equal to 0. He should have subtracted 12 from both sides to get x2 + 7x = 0 before factoring. The correct solutions are 0 and -7.